Managers´ Tales About Developmental Projects: What Makes A Difference When Leading Innovation In Public Sector Services? - Inga Jóna Jónsdóttir 1954- (2013)
Since the economic, financial and social crisis hit most of Western economies, innovation in the public sector has received increased attention. It is putting pressure on public managers to facilitate and lead developmental projects and entrepreneurial new solutions. These pressing external and internal conditions are resolved by constructing and implementing a qualitatively new way of doing things. The study presented in this paper is an ongoing larger narrative-inspired multiple case study, including two new organizations representing transformed workplaces and five developmental work projects in traditional public services in Iceland. The aim is to widen the understanding of the public manager as a leader and facilitator of innovation and collective, innovative learning at work. Central findings reveal the importance of managers’ work-based tacit knowledge as triggers of new concepts. Communication was in all the cases the one most critical success factor behind the collective learning process resulting in an innovative new practice. Keywords: Public Sector Innovation, Practice-based Innovation, Leadership, Learning, Workplace Learning,Communication.